2015
DOI: 10.1111/cp.12059
|View full text |Cite
|
Sign up to set email alerts
|

Family well‐being, parenting, and child well‐being: Pathways to healthy adjustment

Abstract: Family well-being provides a foundation for positive parenting and child well-being. Many previous studies have outlined the possible connections between family well-being, parenting, and child well-being, yet translating research into practice continues to be problematic. The purpose of this article is to review the current literature (from 2000 to 2014) on family and child well-being in order to create a model of well-being that is useful for both researchers and practitioners. The model builds upon Bronfenb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(122 citation statements)
references
References 64 publications
10
105
0
7
Order By: Relevance
“…Results indicated that more consistent parenting approaches and greater use of teaching/explaining (i.e., describing alternative ways of behaving to the child) uniquely predicted better school readiness. These findings are consistent with extensive research underscoring that pedagogy-oriented, child-oriented parenting and discipline are conducive to positive outcomes for children's overall adjustment (Newland, 2015), including school readiness (Dyer et al, 2014;Estrada, Arsenio, Hess, & Holloway, 1987). Given that early learning and literacy activities are commonly cited as direct predictors of children's school readiness (Aldoney et al, 2015;Chazan-Cohen et al, 2009), it was also unsurprising that the current study found greater engagement in these activities at 2-3 years to be predictive of stronger number competence and receptive vocabulary skills at 4-5 years.…”
Section: Other Disciplinary Strategies As Predictors Of School Readsupporting
confidence: 87%
“…Results indicated that more consistent parenting approaches and greater use of teaching/explaining (i.e., describing alternative ways of behaving to the child) uniquely predicted better school readiness. These findings are consistent with extensive research underscoring that pedagogy-oriented, child-oriented parenting and discipline are conducive to positive outcomes for children's overall adjustment (Newland, 2015), including school readiness (Dyer et al, 2014;Estrada, Arsenio, Hess, & Holloway, 1987). Given that early learning and literacy activities are commonly cited as direct predictors of children's school readiness (Aldoney et al, 2015;Chazan-Cohen et al, 2009), it was also unsurprising that the current study found greater engagement in these activities at 2-3 years to be predictive of stronger number competence and receptive vocabulary skills at 4-5 years.…”
Section: Other Disciplinary Strategies As Predictors Of School Readsupporting
confidence: 87%
“…A negative relationship between psychological well-being and power assertive parenting and high levels of physical punishment was also documented [32,33].…”
Section: Positive Family Interactionmentioning
confidence: 91%
“…Power assertive parenting and high levels of physical punishment also decrease psychological well-being [32,33]. Therefore, the purpose of this study was to examine the relationships between Australian nursing student's anxiety, depression, personality and family interaction on their psychological well-being and suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by families that have firm parenting styles, sustained by criteria that instill autonomy for all members and promote adequate, affection-based relationships within the family. These families present the best results in the education of children (Cerezo, et al, 2018;Duncan et al, 2009;Jabagchourian et al, 2014) and it generates between parents and children a high positive effect on the relationship (Gómez et al, 2012;Newland, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been found of how the same component of parental style can be a predictor of different internalization and externalization problems in children, for instance, the use of physical punishment (Chen et al, 2015), lack of communication (Cerezo, Ruiz-Esteban, Sánchez-Lacasa, & Arense-Gonzalo, 2018;Fite, Rubens, Preddy, Raine, & Pardini, 2014), inconsistency and ambiguity in the rules and limits (Jabagchourian, Sorkhabi, Quach, & Strage, 2014). Contrarily, some of these might be protective factors for those problems, such as cohesion, promotion of positive behaviors, emotional competencies, establishment of firm limits, communication and affection (Cenk & Demir, 2016;Gómez et al, 2012;Lakin et al, 2014;Newland, 2015). Therefore, the theoretical position on paternity that underpins the present study is proposed by Duncan, Coastworth and Greenberg (2009).…”
mentioning
confidence: 99%